MOTIVASI DAN KEPATUHAN WAJIB PAJAK ORANG PRIBADI PASCA TAX AMNESTY (STUDI EMPIRIS PADA KPP PRATAMA MANADO) - Wurangian, Mecky; Sondakh, Jullie J.; Manossoh, Hendrik (Universitas Sam Ratulangi, 2021)
This study aims to analyze the compliance and motivation of individual taxpayer participating in 2016 tax amnesty post-tax amnesty The coding analysis method according to Charmaz is used in analyzing the data, with the initial coding and focused coding stages to get the research theme. The results showed that the motivation of individual taxpayers participating in the tax amnesty after the 2016 tax amnesty was spiritual or spiritual motivation or religiosity, motivation to trust the government, and moral motivation. Formal compliance of individual taxpayers participating in the 2016 tax amnesty with profession/occupation as ASN/experts, timely and correct amounts in the Annual SPT report and individual taxpayers participating in the 2016 tax amnesty with profession/ work as UMKM is not timely and not in the right amount in the Annual SPT report. Individual taxpayers with profession/work of ASN/experts and UMKM do not have tax arrears. Individual taxpayers participating in the 2016 tax amnesty post-tax amnesty, both those who have professions/ASN jobs/experts and UMKM, have material compliance willingly and cooperatively if tax officials require tax information. And all tax amnesty participants after the 2016 tax amnesty, both those who have profession/ASN jobs/experts and UMKM have compliance in reporting the Additional Asset Placement Report (LPHT) in the Annual SPT. The relationship of motivation to the compliance of taxpayers participating in the tax amnesty after the 2016 tax amnesty is the link between trust in the government and utilities/incentives.